A determinação da capacidade de troca de cátions do solo e de argilas por meio da troca isotópica com cálcio radioativo - Catani, R. A.; Perez, J. T. (Anais da Escola Superior de Agricultura Luiz de Queiroz, 1965)
This paper describes the determination of cation exchange capacity of soils and clays, by the isotopic exchange method with radioactive calcium. A sample of 5 grams was used for soils and a 1 gram sample for clays. Eight soilsand four clays were studied and five replications for each sample were analysed. The data obtained were: